The Harder They Fall - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2019)
Until a few months ago, the stock market narrative in the United States could have been summarized by the popular acronym BTFD – or `buy the fucking dip'. Analysts and strategists, emboldened by the world's synchronized recovery, Trump's pro-business policies and ample liquidity, predicted that equities would continue rising and recommended that investors take advantage of any temporary weakness to augment their stock holdings in anticipation of further upside. But the atmosphere of boom has since given way to doom and gloom. With equity markets having entered `correction' territory, many observers, including some of the world's richest investors, now warn of a coming crash and a protracted `bear market'. On the face of it, this shifting sentiment has much to do with investors anticipating an earnings reversal. Corporate earnings growth has reached extreme levels from which a downturntrend in profits – and therefore in equity prices – seems imminent. But then, why should forward-looking stock prices be dependent on current earnings in the first place?
Keywords: P16; P1; G01; G; 330; capital as power; capitalized power; stock market; systemic crisis; systemic fear